Odpowiedź :
zad. 3.
[tex]a =2^{\frac{5}{6} } *256^{\frac{1}{3} }*4^{-\frac{5}{2}} = \\ = 2^{\frac{5}{6} } *(2^{8} )^{\frac{1}{3} }*(2^{2}) ^{-\frac{5}{2}} = \\2=^{\frac{5}{6} } *2^{\frac{16}{6} }*2^{-5} = \\=2^{\frac{21}{6} }*2^{-5} = \\=2^{-1\frac{1}{2} }[/tex]
[tex]a =2^{-1\frac{1}{2} }[/tex]
________
[tex]b=64^{-\frac{1}{3} } *32^{-\frac{1}{2} } *16^{\frac{3}{2} } =\\= (2^{6}) ^{-\frac{1}{3} } *(2^{5}) ^{-\frac{1}{2} } *(2^{4}) ^{\frac{3}{2} } =\\= 2^{-2}*2 ^{-\frac{5}{2} }*2^{6}= \\= 2 ^{1\frac{1}{2} }[/tex]
[tex]b= 2 ^{1\frac{1}{2} }[/tex]
_______
[tex]b^{-1} = (2 ^{1\frac{1}{2} })^{-1}= 2 ^{-1\frac{1}{2} } =a[/tex]
zatem [tex]a= b^{-1}[/tex]
odp.B
zad.4.
[tex]((4+3*2^{\frac{1}{2} })^{2})^{\frac{1}{2} } - ((4-3*2^{\frac{1}{2} })^{2})^{\frac{1}{2} } = (4+3*2^{\frac{1}{2} })^{1} - (4-3*2^{\frac{1}{2} })^{1} = \\= 4+3*2^{\frac{1}{2} } - 4+3*2^{\frac{1}{2} } = 6*2^{\frac{1}{2} }[/tex]
odp. C